TEOLOGI ISLAM KONTEMPORER: TELAAH PEMIKIRAN TEOLOGI DAN PENDIDIKAN ISLAM AHMAD SURKATI MELALUI AL-IRSYAD DI INDONESIA - Al Hamimy, Muhammad Faishol; Prayogi, Rizal Mifthakul (LPPI Universitas Al-Qolam Malang, 2025)
This article aims to examine the theological renewal introduced by Ahmad Surkati through the Al-Irsyad organization in Indonesia. Using a qualitative approach and literature review method, this study relies on sources such as books, journals, and other relevant documentation. The research process involved collecting, analyzing, verifying, and synthesizing data to reveal the renewal ideas proposed by Surkati. The results show that Al-Irsyad was founded in response to social inequality in Jami'at Khair, with Ahmad Surkati's thinking influenced by the reformist figure Muhammad Abduh. Al-Irsyad promotes renewal in two main areas: religion and education. In the field of religion, this organization is committed to purifying Islamic teachings, opposing deviant practices, and promoting the principle of social equality among Muslims. In the field of education, Al-Irsyad focuses on developing a scientific culture that balances religious and worldly knowledge, as well as preparing Muslims to face the challenges of the times. Through this movement, Surkati succeeded in introducing the concept of equality among Indonesian Muslims and laid the foundation for the modernization of Islamic understanding relevant to the social and global context. Keywords: Islamic Modernization, Ahmad Surkati, Al-Irsyad, Islamic Theology, Islamic Education